Segmented Filamentous Bacteria – Metabolism Meets Immunity - Hedblom, Grant A.; Reiland, Holly A.; Sylte, Matthew J.; Johnson, Timothy J.; Baumler, David J. (Frontiers in Microbiology, 2018)
Segmented filamentous bacteria (SFB) are a group of host-adapted, gut commensal organisms that attach to the ileal epithelium of vertebrate and invertebrate hosts. A genetic relative of the genus Clostridium, these morphologically unique bacteria display a replication and differentiation life cycle initiated by epithelial binding, making it difficult to culture these bacteria in vitro. SFB intimately bind to the surface of absorptive intestinal epithelium without inducing an inflammatory response. Rather, their presence impacts the generation of innate and acquired immunity and clearance of extracellular bacterial or fungal pathogens in the gastrointestinal and respiratory tracts. SFB have recently garnered attention due to their role in promoting adaptive and innate immunity in mice and rats through the differentiation and maturation of Th17 cells in the intestinal tract and production of immunoglobulin A (IgA) and stimulating the differentiation and maturation of Th17 cells. SFB are the first commensal bacteria identified that impact the maturation and development of Th17 cells in mice. Recently, microbiome studies have revealed the presence of Candidatus Arthromitus (occasionally designated as Candidatus Savagella), a proposed candidate species of SFB, in higher proportions in higher-performing flocks as compared to matched lower-performing flocks, suggesting that SFB may serve to establish a healthy gut and protect turkeys from pathogens resulting in morbidity and decreased performance. In this review we seek to describe the life cycle, host specificity, and genetic capabilities of SFB and how these factors influence the host immunity and microbiome. Although the role of SFB to induce antigen-specific Th17 cells in poultry is unknown, they may play an important role in modulating the immune response in the intestinal tract to promote resistance against some infectious diseases and promote food-safety. This review will serve to demonstrate the importance of studying and further characterizing commensal, host-specific bacteria, as many animal studies have demonstrated their importance to host health.